Path Planning Optimization For Solar-Powered Perpetual Flight Across The World - Lim, Guang Ming (Universiti Sains Malaysia, 2018)
Unmanned Aerial Vehicle (UAV) has been widely used for mapping purposes recently in the agricultural, military and geographic information fields which covered small area. Researches on the solar power management strategy and enhancement of mission profiles have been done by the researchers around the world to prolong the endurance (mission duration) of the UAV. The technologies and strategies studied show the possibility for an UAV to perform solar-powered perpetual flight for mapping purpose across the world. In this research, the factors affecting the solar-powered flight such aselevation, density and solar irradiance available are studied. A validated algorithm with overall error percentage less than 10 % is developed to simulate the solar-powered flight.Next, the detailed path planning is planned which allow an UAV to perform mapping mission at constant altitude, 600 m above the Earth’s surface with minimized geometric error without fail. The successful flight pattern done by (Tan) which has covered latitude of ±66 ºat various longitude is used in this research with the attempt to reach the global coverage. Different combination of launching location and date time are simulated and studied based on the solar irradiance available from different regions. The results of the study are determined and displayed in terms of the perpetuality for the perpetual flight across the world. The findings of the simulation show that the solar-powered flight has the highest perpetuality (24.7%) or highest endurance (24364 hours) by launching at longitude 115 W of North America region in January and February. Study on launching multiple UAVs should be carried out to further investigate the interest of completing a global coverage mission in a shorter duration.